Design of a linearized 4-H-bridge STATCOM for load balancing purposes - Obais, Abdulkareem Mokif; Mukheef, Ali Abdulkareem (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
In this paper, a 4-H-bridge STATCOM (4-HB STATCOM) is introduced. Four H-bridges are cascaded to build the proposed STATCOM. Cascading the H-bridges makes it possible to operate the devised STATCOM on high voltage levels with less voltage harmonic association. The proposed STATCOM is equipped with an adaptive current controller and a voltage balancing technique for its DC capacitor voltages. The adopted controlling strategy makes the STATCOM respond continuously and linearly to current demand in both inductive and capacitive operational modes without noticeable association of harmonics. The DC capacitor of each H-bridge is shunted by a second harmonic filter to stabilize its voltage. The proposed STATCOM does not require initial charging of its DC capacitors because it is provided with a utilized technique for charging them rapidly by disabling the STATCOM carrier for a certain period sufficient to build up the required level of DC voltages. In this work, the proposed STATCOM is designed to operate on 11 kV AC voltage as a continuously and linearly controlled compensating susceptance. It can deservingly be employed in load balancing systems for achieving big amount of energy savings in power generation and big reduction in transmission losses.